The mobile phone "ecosystem" in Africa - (:unkn) unknown (My University, 2013)
Panel ICT and networks in Africa, mod. Gina Porter, Thomas Molony, Marie‐Soleil Frère, Marloes Hamelink http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2322
Keywords: African Research